Bayesian and Non-Bayesian Estimators of the Parameters of Weibull Distribution - Abtisam J. Kadhim; Huda A. Rasheed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, some estimators for the shape and scale parameters of Weibull distribution have been obtained using Maximum likelihood as non-Bayesian estimators, as well as Bayes estimators. Bayesian estimations have been obtained under Scale invariant and Entropy loss functions based on exponential priors. Lindley’s approximation has been used effectively in Bayesian estimation. Based on the Monte Carlo simulation method, those estimators are compared depending on the mean squared errors (MSE’s).